Analysis on the Embodiment of OBE in Cultivation of Business English Majors - Tian, Zhi (Pacific International Journal, 2022)
OBE concept is highly accepted in talent cultivation today. It attaches great importance to learning results, and its "four points" are highly matched with cultivation of application-oriented specialty. As such a specialty, Business English major stresses that its talent training specifications must meet the needs of learners and employers, and clearly stipulate the learning achievements of the major. Therefore, in the process of talent cultivation there are also “four points” that must be considered and realized to strictly implement and achieve "maximum ability", including how to define the learning outcomes of business English majors, why to define them in this way, and what ways to effectively help students achieve these learning outcomes and evaluate the learning outcomes that students have achieved.